Evaluation of Lead(II) Adsorption on A Column Packed With Phosphorylated Tamarind Nut Carbon - SUGANTHI, N.; SRINIVASAN, K. (Asian Journal of Chemistry, 2010)
The continuous adsorption of lead ions from aqueous solutions on phosphorylated tamarindnut carbon and commercial activated carbon was studied. The aim of carrying the continuous flow studies is to assess the effect of pH, flow rate and bed height on the adsorption of lead ion. This has helped in ascertaining the practical applicability of the adsorbent in large scale. The effect of common anions and cations on adsorption of lead ions was examined. The regeneration capacity of carbons was analyzed by repeated adsorption and desorption processes. Breakthrough capacities were found out using wastewater containing lead ions and phosphorylated tamarindnut carbon was found to be superior to commercial activated carbon in the removal of lead ions.